Scrabble Game in Students’ Reading Comprehension - Tasya, Siti Hanna; Mutiarani, Mutiarani (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2024)
Abstract The purpose of this research is to explore the effectiveness of scrabble game in students’ reading comprehension achievement. One class of 7th graders composing 27 students of MTs Jami’iyyah, Pondok Aren, South Tangerang, participated In this as samples. This research applied quantitative method with pre-experimental design of one group pretest and posttest. The instruments used in collecting the data were pretest and posttest. There were 25 multiple choice questions given in each test to be done by the students in 50 minutes. A quantitative analysis was firstly taken before computing the data by using statistical analysis of paired sample t-test. The calculation showed that the average score of students’ reading comprehension post-test was higher (83.77) than in the pretest (56.22). Besides, the statistical analysis indicated that the significant value of 0.01 < a (0.05), thus, Ha was accepted. Referring to the analysis results above, this research concluded that scrabble game was effective media to be used in improving reading comprehension skill of the students. Abstract The purpose of this research is to explore the effectiveness of scrabble game in students’ reading comprehension achievement. One class of 7th graders composing 27 students of MTs Jami’iyyah, Pondok Aren, South Tangerang, participated In this as samples. This research applied quantitative method with pre-experimental design of one group pretest and posttest. The instruments used in collecting the data were pretest and posttest. There were 25 multiple choice questions given in each test to be done by the students in 50 minutes. A quantitative analysis was firstly taken before computing the data by using statistical analysis of paired sample t-test. The calculation showed that the average score of students’ reading comprehension post-test was higher (83.77) than in the pretest (56.22). Besides, the statistical analysis indicated that the significant value of 0.01 < a (0.05), thus, Ha was accepted. Referring to the analysis results above, this research concluded that scrabble game was effective media to be used in improving reading comprehension skill of the students.